Hesperidin in orange juice improves human endothelial function in subjects with elevated blood pressure and stage 1 hypertension: A randomized, controlled trial (Citrus study) - Valls, Rosa M.; Pedret, Anna; Calderón-Pérez, Lorena; Llauradó, Elisabet; Pla-Pagà, Laura; Companys, Judit; Moragas, Ana; Martín-Luján, Francisco; Ortega, Yolanda; Giralt, Montse; Rubió, Laura; Canela, Núria; et al. (Journal of functional foods, 2021)
[Display omitted] •Hesperidin enriched orange juice improves human endothelial function.•Endothelial function improves both at postprandial and after sustained intake.•Endothelial function improvement was directly linked to hesperidin content of drinks.•Hesperidin enriched orange juice improves inflammatory status.•Hesperidin enriched orange juice induces beneficial changes at transcriptomic level. In a randomized, parallel, double-blind, placebo-controlled trial, participants with elevated blood pressure and stage 1 hypertension (n = 159) received 500 mL/day of control drink, orange juice (OJ), or hesperidin-enriched OJ (EOJ) for 12-weeks, and their ischaemic reactive hyperemia (IRH) was assessed at baseline and after 4, 8, and 12-weeks. Two dose–response studies were nested within the sustained-consumption study: at baseline and after 12-weeks, a single dose of 500 mL was administered. All treatments increased postpandrial IRH, and a higher increase was obtained with EOJ. Moreover, hs-CRP and IL6 increased but not after EOJ. After 12 weeks of sustained consumption: IRH values after EOJ increased versus control group; EOJ treatment increased DSP and decreased IEX-1 gene expression in PBMCs; and IRH directly correlated to NO and inversely to MPO and IEX1. Thus, hesperidin in OJ improves human endothelial function, lower inflammatory status at systemic level and changes at transcriptomic level might account for the increased IRH observed.